Tracheobronchial calcification associated with Keutel syndrome - (:unkn) unknown (TURKISH J PEDIATRICS, 2006)
Tracheobronchial cartilage calcification is an unusual radiologic finding in infants and children under 15 years old. Keutel syndrome is a rare, autosomal recessive disorder characterized by diffuse cartilage calcification, brachytelephalangia, pulmonary stenosis and midfacial hypoplasia. We report two children in whom abnormal tracheobronchial calcification was associated with Keutel syndrome. Keutel syndrome should be considered in the differential diagnosis of children with tracheobronchial calcification.
Keywords: tracheobronchial calcification; Keutel syndrome; brachytelephalangia; CARTILAGE CALCIFICATION; CHILDREN